Measuring banks’ market power in the presence of economies of scale: A scale-corrected Lerner index - Spierdijka, Laura; Zaourasa, Michalis (Journal of Banking & Finance, 2018)
A positive Lerner index indicates a welfare loss for consumers due to deviations from marginal-cost pricing. Such a welfare loss may not always be due to market power, though. In particular, marginal-cost pricing would result in negative profit for the firm in the presence of economies of scale. In such a scenario, a positive Lerner index could simply reflect the firm’s need to earn non-negative profits rather than market power. We propose a novel, scale-corrected price-cost margin for firms that produce in the economies of scale range. We show that this measure is more informative about market power than the Lerner index itself. As an empirical illustration, we analyze market power in the U.S. banking sector using both the corrected and uncorrected Lerner index. The corrected Lerner index reveals significant market power for U.S. commercial banks during the 2000 – 2014 period.